Students’ Perception of the Use of Cooperative Learning Approach in Writing Class for Narrative Text Learning - Riyana, Arfah; Aflahah, Noor Aida; Al Farhan, Miftah (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2025)
Cooperative learning is a teaching approach that places students in groups to work together to complete learning targets. Many studies have focused on the implementation of cooperative learning in the classroom. However, only few studies discuss using cooperative learning in the writing classroom on narrative text learning from the student’s perspective. This research aims to find out students’ perceptions of the use of cooperative learning in narrative text learning and the implementation of cooperative learning in teaching writing in narrative text learning. Using a qualitative method with the case study approach, this research was conducted in one of the private schools in Banjarmasin, with six students and a teacher as participants. This study used classroom observation and interviews in data collection and documentation as an additional instrument to describe cooperative learning in writing classes for narrative learning. The results of this study confirmed that most students positively agree with the use of cooperative learning in terms of group collaboration, discussion, and information exchange in the classroom. However, time consumption factor was a major concern for students with the highest score. In spite of these findings, further studies are needed to expand the scope of using cooperative learning in the teaching of integrated language skills in the classroom.